SOCIAL-PHILOSOPHICAL FOUNDATIONS OF ECOLOGICAL RATIONALITY IN THE SYSTEM OF STATE AND SOCIAL POLICY OF UZBEKISTAN (Western European Journal of Historical Events and Social Science, 2026)
This article analyzes the formation and development of the concept of ecological rationality in the system of state and social policy of the Republic of Uzbekistan from a socio-philosophical perspective. Ecological rationality is interpreted as an important component of the sustainable development paradigm, and its role in the system of state governance, economic policy, civil society institutions and social consciousness is revealed. The results of the study substantiate the need to integrate ecological responsibility and rational decision-making mechanisms